Environmental Awareness: Analysis of Junior High School Students - Balgis Az Zahra; Rini Solihat; Lilit Rusyati (FKIP UNIVERSITAS PAKUAN, 2025)
This study aimed to analyze students’ environmental awareness of Junior High School Students. The research was conducted by descriptive study with the research subjects consisted of 107 students grade IX. The environmental awareness measured consisted of three factors which are cognitive, emotional and behaviour. The data were obtained using a valid and reliable instrument consisted of 18 questionnaire statements. Data was then analyzed and compared within two variables which are gender (male and female) and science cognitive score (high and low achiever) by using simple statistical analysis and Mann-Whitney test. The result showed that first, students’ environmental awareness is categorized as medium to good. Second, there is no significant difference between male and female. However, female students showed slightly higher environmental awareness than the male. Third, there is no significant difference between high and low achiever. However, high achiever students gained slightly higher score in their environmental awareness.